Developing integrated pedagogical approaches in play pedagogy: Malaysian experiences - Norsuhaily, Abu Bakar; Abdul Hakim, Abdullah; Nadhirah, Nordin (Canadian Center of Science and Education, 2015)
This paper examines contemporary developments in play and pedagogy in early childhood education settings, drawing on Malaysian policies and international play scholarship. The study explores and analyses some of the challenges inherent to incorporating play into classroom practice, which is occurring in four types of preschool classroom settings in Malaysia. It investigates the implementation of play in each of these settings. Established principles about play and learning are reified in many curriculum guidelines, alongside recommendations for the role of adults in linking play provision with their pedagogical strategies. Play is also located within contemporary discourses about quality and effectiveness, with a specific focus on ‘educational’ play (Wood, 2010). Although policy texts and policy-oriented research have provided positive validations for play as integral to ‘effective practice’, there remain significant challenges in conceptualizing the play-pedagogy relationship. Linking play with defined educational outcomes and effectiveness agendas also raises questions about the regulation of play through dominant policy discourses and practices. Drawing on critical and post developmental theories, some of the key principles underpinning play and pedagogy are scrutinized here. It will be argued that some of the essential truths about play can also be seen as myths, which need to be contested in the light of contemporary concerns with diversity, power and control and how these relate with educational settings.